Language planning and language policy in the ecological perspective - Wiertlewska, Janina (Glottodidactica, 2012)
The paper deals with the issue of language planning and policy both in the historical as well as the ecological perspective. The problem of linguistic diversity protection and maintenance in opposition to monolingual global world is explored.